2013
DOI: 10.1002/jbm.a.34653
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of oxidized hyaluronic acid/resveratrol hydrogel for cartilage tissue engineering

Abstract: Osteoarthritis is a type of arthritis that is caused by breakdown of cartilage, with eventual loss of the cartilage of the joints. The ability of self-repair in damaged cartilage tissue is limited; the aim of this work is to fabricate and characterize an oxidized hyaluronic acid/resveratrol (Oxi-HA/Res) hydrogel for future applications in cartilage tissue engineering. Under physiological conditions, the Oxi-HA/Res hydrogel was prepared by chemical crosslinking of Oxi-HA with resveratrol solution and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…For these reasons, it is of clinical significance to find natural remedies to inhibit the release of these pro-inflammatory cytokines. In this research, antiinflammatory scaffolds (Coll/PAA-Res) showed an enhanced ability to capture DPPH free radicals, and eventually offered a protective effect on the chondrocytes and BMSCs in a ROS environment, as reported previously [16,20]. Then, an acute trauma defect in the rabbit joint was created to evaluate the anti-inflammatory effect of the Coll/PAA-Res scaffold.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…For these reasons, it is of clinical significance to find natural remedies to inhibit the release of these pro-inflammatory cytokines. In this research, antiinflammatory scaffolds (Coll/PAA-Res) showed an enhanced ability to capture DPPH free radicals, and eventually offered a protective effect on the chondrocytes and BMSCs in a ROS environment, as reported previously [16,20]. Then, an acute trauma defect in the rabbit joint was created to evaluate the anti-inflammatory effect of the Coll/PAA-Res scaffold.…”
Section: Discussionmentioning
confidence: 89%
“…S.2) suggested that the Res was incorporated into Coll. Compared with the pure Coll scaffold, the peaks at 1147 and 950 cm À1 separately attributable to the CAO stretch of phenol and the CAH stretch of the benzene ring in Res [16,25] appear in Coll/PAA-Res.…”
Section: Properties Of the Scaffoldsmentioning
confidence: 95%
See 2 more Smart Citations
“…Resveratrol exerts its chondroprotective function in human chondrocytes in vitro by deactivating p53-induced apoptosis [165] or inhibiting IL-1b-induced apoptosis [166]. Evidence shows that oxidized hyaluronic acid/resveratrol hydrogel is a promising cell carrier for chondrocytes to repair cartilage defects [167].…”
Section: Osteoarthritismentioning
confidence: 99%